2000
DOI: 10.3758/bf03209337
|View full text |Cite
|
Sign up to set email alerts
|

What is free association and what does it measure?

Abstract: This paper reports the results of a study of free association in which participants were asked to produce the first two words to come to mind. The findings were used to estimate the reliability of indices of strength and set size for different types of items and to model free association as a retrieval task. When confined to first responses, reliability was generally high for both indices, particularly for words with smaller sets of associates and stronger primaries. When second responses were included, reliab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
213
2
11

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 219 publications
(230 citation statements)
references
References 50 publications
4
213
2
11
Order By: Relevance
“…Moreover, we experimented with three versions of word associations: 1) similarities calculated using only the first response of each participant; 2) similarities obtained using the first three responses at most, as in De Deyne et al (2013); and 3) all the responses obtained. We observed that taking into account the first three and all responses yielded higher correlations with corpus data than taking only the first response, in line with the findings of Nelson et al (2000) and De Deyne et al (2013). Overall, higher correlations were obtained when taking into account just the first three responses.…”
Section: Comparison Of Both Approachessupporting
confidence: 80%
See 2 more Smart Citations
“…Moreover, we experimented with three versions of word associations: 1) similarities calculated using only the first response of each participant; 2) similarities obtained using the first three responses at most, as in De Deyne et al (2013); and 3) all the responses obtained. We observed that taking into account the first three and all responses yielded higher correlations with corpus data than taking only the first response, in line with the findings of Nelson et al (2000) and De Deyne et al (2013). Overall, higher correlations were obtained when taking into account just the first three responses.…”
Section: Comparison Of Both Approachessupporting
confidence: 80%
“…It is generally acknowledged that these relations have a broad semantic basis (Nelson et al 2000;Roediger et al 2001;McRae et al 2012;Brainerd et al 2008). Evidence suggests that we might find typical relations such as hyponymy, synonymy and antonymy (Clark 1970), although other types of relations such as cause-effect or part-whole (Hernández et al 2014) and thematic relationships (Peirsman and Geeraerts 2009) are more frequent.…”
Section: Background On Similaritymentioning
confidence: 99%
See 1 more Smart Citation
“…Esta análise foi realizada após excluírem-se as respostas do tipo "não sei". A força de associação corresponde à maior probabilidade de uma resposta ocorrer em detrimento de outras, dada uma palavra-alvo específica (Nelson, McEvoy, & Dennis, 2000). A força de associação das palavras da lista variou entre 6 e 90 %.…”
Section: Resultsunclassified
“…Na análise do tamanho do conjunto de associados semânticos diferentes gerados para cada palavra-alvo, quando considerado o tamanho total do conjunto houve uma (Nelson et al, 2000;Nelson & Schreiber, 1992;Van Erven & Janczura, 2004). A análise de correlações entre os fatores mostrou que quanto maior a força de associação semântica entre as palavras menor é o tamanho do conjunto gerado, total e significativo.…”
Section: Discussionunclassified